Wind quality designation concept and application - Şen, Zekai; Serencam, Uğur (Wiley, 2021)
Generally, wind energy production is based on the average wind speed without any classification. This article proposes a classification system on the basis of wind speed durations greater than a given threshold value. For this purpose, the wind quality designation (WQD) concept is defined based on the wind potential duration, amount, and intensity on a threshold level. Its classifications are depicted on five risk percentage classes as "excellent," "very good," "good," "fair," and "weak. Apart from the classification, the change of WQD with wind speed threshold provides qualitative and quantitative wind speed energy production assessment. The specific objective of the article is to present theoretical WQD explanations on the basis of the most frequently employed two-parameter Weibull probability distribution function (PDF). The application is provided for Adiyaman City, Kahta meteorology station wind speed records from the Southeastern province of Turkey. It is noticed that there is no "Weak" category at this station and the most effective quality class is "Excellent" from 14 m/s to almost 27 m/s wind speeds. The average wind speed corresponds to about 62% WQD. Finally, the wind speed potential durations PDF abides by the logarithmic-normal PDF, whereas amount and intensity accord with the Weibull PDFs.
Keywords: Designation; Potential; Probability; Quality; Risk; Weibull; Wind